Rate and Predictors of Endoscopic Mucosal Healing in Biologic Naive Patients with Inflammatory Bowel Disease by Azathioprine Treatment: A Real World, 10 Years- Experience from a Single Centre in Turkey. - Basaranoglu, METİN; BAŞARANOĞLU, METİN; Ertan, A; Mathew, S; Najjar, SM; Senturk, H; Ala, A; Demirbag, AE; ŞENTÜRK, HAKAN (My University, 2016)
Background: There is increasing evidence that endoscopic mucosal healing (EMH) is a key target in inflammatory bowel disease (IBD) therapy. However, there is limited evidence of EMH rates with conventional IBD therapy outside of Western population groups. Ai̇m: To evaluate the role of azathioprine (AZA) in inducing EMH in IBD patients. Methods: Patients with inflammatory bowel disease were evaluated in terms of endoscopic mucosal healing and the incidence of surgical interventions during the azathioprine treatment between 1995 to 2014. Results: A total of 120 inflammatory bowel disease patients were enrolled. Endoscopic mucosal healing was found in 37% patients with inflammatory bowel disease (42% in chronic ulcerative colitis and 33% in Crohn's disease). Male gender had a negative impact on the efficacy of azathioprine (P<0.05). Responder inflammatory bowel disease patients were older (age at the IBD diagnose) than the nonresponder (P<0.05). Azathioprine therapy reduced the number of the surgical interventions (P<0.05). Conclusi̇on: We showed that azathioprine therapy significantly induced endoscopic mucosal healing in biologic naïve patients with active inflammatory bowel disease as well as decreasing the surgical interventions, with negative predictive factors identified by a younger age at IBD presentation and male gender.